Evaluation of the diagnostic accuracy of a typhoid IgM flow assay for the diagnosis of typhoid fever in Cambodian children using a Bayesian latent class model assuming an imperfect gold standard - Moore, C; Pan-Ngum, W; Wijedoru, L; Sona, S; Nga, T; Duy, P; Vinh, P; Chheng, K; Kumar, V; Emary, K; Carter, M; White, L; et al. (American Society of Tropical Medicine and Hygiene, 2014)
Rapid diagnostic tests are needed for typhoid fever (TF) diagnosis in febrile children in endemic areas. Five hundred children admitted to the hospital in Cambodia between 2009 and 2010 with documented fever (≥ 38°C) were investigated using blood cultures (BCs), Salmonella Typhi/Paratyphi A real-time polymerase chain reactions (PCRs), and a Typhoid immunoglobulin M flow assays (IgMFAs). Test performance was determined by conventional methods and Bayesian latent class modeling. There were 32 cases of TF (10 BC- and PCR-positive cases, 14 BC-positive and PCR-negative cases, and 8 BCnegative and PCR-positive cases). IgMFA sensitivity was 59.4% (95% confidence interval = 41–76), and specificity WAS 97.8% (95% confidence interval = 96–99). The model estimate sensitivity for BC was 81.0% (95% credible interval = 54–99). The model estimate sensitivity for PCR was 37.8% (95% credible interval = 26–55), with a specificity of 98.2% (95% credible interval = 97–99). The model estimate sensitivity for IgMFA (≥ 2+) was 77.9% (95% credible interval = 58–90), with a specificity of 97.5% (95% credible interval = 95–100). The model estimates of IgMFA sensitivity and specificity were comparable with BCs and better than estimates using conventional analysis.